Simple promotion of Cas9 and Cas12a expression improves gene targeting via an all-in-one strategy - Cheng, Yiqiu; Zhang, Lei; Li, Jing; Dang, Xiaofei; Zhu, Jian-Kang; Shimada, Hiroaki; Miki, Daisuke (Frontiers in Plant Science, 2024)
Gene targeting (GT) is a promising tool for precise manipulation of genome sequences, however, GT in seed plants remains a challenging task. The simple and direct way to improve the efficiency of GT via homology-directed repair (HDR) is to increase the frequency of double-strand breaks (DSBs) at target sites in plants. Here we report an all-in-one approach of GT in Arabidopsis by combining a transcriptional and a translational enhancer for the Cas expression. We find that facilitating the expression of Cas9 and Cas12a variant by using enhancers can improve DSB and subsequent knock-in efficiency in the Arabidopsis genome. These results indicate that simply increasing Cas protein expression at specific timings - egg cells and early embryos - can improve the establishment of heritable GTs. This simple approach allows for routine genome engineering in plants.